An observatory plot system for grain production in the Neotropical savannas - Parsa, Soroush; Gómez Naranjo, Jaime; Alba-Quijano, Diego Alejandro; Aguilar-Ariza, Andrés; Gómez Mora, Juan David; Guevara, Edward D.; Bernal Riobo, Jaime Humberto (Hindawi Limited, 2015)
The neotropical savanna is the second largest biome in South America, with significant potential for agricultural development. In Colombia, this biome is experiencing rapid land-use change leading to the conversion of seminatural landscapes into to intensive agricultural systems. Our Dataset Paper documents the emerging intensive grain production systems. Between 2011 and 2013, we established 336 observatory plots within farmer’s maize, rice, and soybean fields along a 200 Km transect from Puerto Lopez (Meta) to Viento (Vichada). From each of these plots, we submit 184 descriptors or variables capturing their location, rotation history, management, and environment. Our specific objective in collecting the data was to identify key factors explaining yield variation, with emphasis on interactions between management and environmental factors potentially informing the development of site-specific management protocols. Beyond this objective, the dataset submitted here is intended to support additional inquiries contributing to the sustainable development of agriculture in the neotropical savannas.